Pengaruh Minat Konsumen dan Harga Produk terhadap Pengambilan Keputusan Konsumen dalam Pembelian Produk - Gusti Winurma; Wahyu Dewi Hapsari (SAFE-Network, 2024)
In the current era of globalization there are many changes to world industry which is increasingly developing. This is because of the flow of globalization which is increasingly wide open for every business actor. Consumers are an important factor in increasing the SME index. Their desires are not always straight, sometimes they turn very quickly not according to the time when they want to buy the product. Consumers are often faced with needs, such as basic necessities, children's school fees, and falling currencies which influence people in purchasing aluminum products. Sp Aluminum is a company that operates in the aluminum industry with several stages such as casting, aluminum smelting and making household equipment and crafts. There are various types of products at Sp Aluminum, namely accessories, frying pans, cauldrons and pans. Based on this description, this research aims to determine the influence of consumer interest and product price on consumer decision making in purchasing Sp Aluminum Yogyakarta products. This research is quantitative, the sample in the research is all consumers who will buy products or who have ever bought products at Sp Aluminum Yogyakarta, which consisted of 50 respondents. The data collection technique uses a questionnaire. The results of this research found that consumer interest has a positive and significant effect on purchasing decisions for Sp Yogyakarta aluminum products. Product price has a positive and significant effect on purchasing decisions for Sp Aluminum Yogyakarta products.